The Association between Regional Fat Distribution and Acute Mountain Sickness in Young Hikers - Dobrosielski, Devon A.; Guadagno, Michelle; Phan, Phillip (Sports Medicine International Open, 2017)
Acute mountain sickness (AMS) can occur upon rapid ascent from low to high altitude. This study examined the association between central adiposity and the development of AMS in young adults during a high-altitude hike. Total and regional body fat were measured at sea level using dual-energy X-ray absorptiometry. Within 24 h of arriving in Cusco, Peru (3 400 meters) participants embarked on a 14-mile hike across the Andes Mountain range in southern Peru. Symptoms of AMS were assessed using the Lake Louise score at 24 h (3 400 meters), 29 h (4 100 meters), 34 h (3 800 meters) and 53 h (2 900 meters). 14 participants (mean age 21±2 years; women: 11, men: 3) completed the study. The number of participants exhibiting at least mild AMS increased from 6 (54%) at 3 400 meters to 9 (64%) at 3 800 meters. A higher AMS score at 4 100 meters was associated with greater android (r=0.72, p<0.01), trunk (r=0.73, p<0.01) and total body (r=0.71, p<0.01) fat, but not with total body fat % (r=0.39, p=0.16). Our findings suggest that central obesity, but not total body fat per se, may be an important factor in the development of AMS.